Pengaruh Motivasi Kerja dan Budaya Kerja Terhadap Produktivitas Kerja Karyawan di Kebun Huta Padang PT. Perkebunan Nusantara III (PERSERO) Kabupaten Asahan Sumatera Utara - Gozali, Luli Achmad; Lubis, Yusniar; Syaifuddin, Syaifuddin (Universitas Medan Area, 2020)
This study is aimed to determine and analyze the effect of the implementation of motivation and culture on the employees productivity at Huta Padang estate of PT. Perkebunan Nusantara III (Persero) Asahan Regency North Sumatera. This research method uses a quantitative approach, the type of research is a survey. The sample was determined by stratified random sampling method, 95 people. The data collection through questionnaires. Data were analyzed using multiple linear regression. The results showed that partially and simultaneously, the implementation of motivation and culture had a positive and significant effect on the employess productivity at Huta padang estate of PT. Perkebunan Nusantara III (Persero) Asahan Regency North Sumatera. The determination coefficient value of 0.882, indicates that the influence of the implementation of motivation and culture on the employess productivity of Huta Padang estate of PT. Perkebunan Nusantara III (Persero) Asahan Regency North Sumatera is 88.2%. The culture has more dominant influence on the employees produktivity atÂ Huta Padang estate of PT. Perkebunan Nusantara III (Persero) Asahan Regency North Sumatera, with a direct influence of 73,2%.Â